The effect of the dimensions of transformational leadership style on the level of organizational values: A case study of a sample of workers at the University of Medea - Hiba Kadandal; Ali Abdelallah (Dirassat Journal Economic Issue, 2016)
The principal objective of this research on the validation key premise revolves around a relationship between transformational leadership dimensions (charismatic effect, individual attention, intellectual stimulation, stimulation) and the level of organizational values ​​(management, management values, mission management values, relationship management and environmental values) , and this is by conducting a prospective study on a sample (30 individual) workers at the University of Medea. And has been getting needed to test this hypothesis by using data from a questionnaire distributed to the sample and the results were analyzed by SPSS software. And it has reached this search to a group of the most important results that there is a positive correlation and a statistically significant differences between the various organizational and transformational leadership dimensions of values, with some recommendations that serve the search.